A new malyngamide from the marine cyanobacterium Moorea producens. Issue 1 (2nd January 2018) - Jiang, Weina; Zhou, Wei; Othman, Raymie; Uchida, Hajime; Watanabe, Ryuichi; Suzuki, Toshiyuki; Sakamoto, Bryan; Nagai, Hiroshi
Abstract: A new malyngamide (1 ) was isolated along with seven known compounds (2 –8 ) from the marine cyanobacterium Moorea producens collected in Hawaii. Compound1 represented the first reported malyngamide with a hydroxy moiety at C-7 of the characteristic fatty acid portion of the compound. Compound1 showed cytotoxicity against L1210 cell line at an IC50 value of 2.9 mM and lethal toxicity against the shrimp Palaemon paucidens at a LD100 value of 33.3 mg/kg. The bioactivity of compound1 was approximately 10–100 times weaker than those of isomalyngamides A and B (3, 4 ). These results indicated that the methoxy group at C-7 of the fatty acid section confers a degree of bioactivity in malyngamides. Abstract :